Enhancement of Thermal Stability and Cycling Performance of Lithium-Ion Battery at High Temperature by Nano-ppy/OMMT-Coated Separator. (15th February 2017) - Yang, Shuo; Qin, Huiya; Li, Xuan; Li, Huijun; Yao, Pei
Abstract : Nanopolypyrrole/organic montmorillonite- (nano-ppy/OMMT-) coated separator is prepared by coating nano-ppy/OMMT on the surface of polyethylene (PE). Nano-ppy/OMMT-coated separator with three-dimensional and multilayered network structure is beneficial to absorb more organic electrolyte, enhancing the ionic conductivity (reach 4.31 m S · c m - 1 ). Meanwhile, the composite separator exhibits excellent thermal stability and mechanical properties. The strong covalent bonds (Si-F) are formed by the nucleophilic substitution reaction between F − from the thermal decomposition and hydrolysis of LiPF6 and the covalent bonds (Si-O) of nano-ppy/OMMT. The Si-F can effectively prevent the formation of HF, POF3, and LiF, resulting in the inhibition of the disproportionation of Mn 3+ in LiNi1/3 Co1/3 Mn1/3 O2 material as well as reducing the internal resistance of the cell. Therefore, the nano-ppy/OMMT-coated separator exhibits outstanding capacity retention and cycling performance at 80°C.